Peran Perempuan Dalam Pewarisan Tradisi Kitab Kuning Pada Madrasah Perti di Minangkabau Pasca Kemerdekaan - Erman (Khazanah: Jurnal Sejarah dan Kebudayaan Islam, 2019)
The research aimed to analyze the social reality which has sympathized for the women role on the inheritance of the kitab kuning tradition in Minangkabau. The reality was formed in Madrasah Perti (MTI Candung and MTI Pasir) that has opened competition markets to women since the beginning of the 20th century to get the influence and legitimacy at inheritance of classical Islamic tradition. As a social field, Madrasah Perti is a place of interaction, socialization and internalization to form intellectual capital that enabled women to reproduce a wider role on the inheritance of the kitab kuning tradition in Minangkabau after Independence.